An Evaluation of the Large‐Scale Atmospheric Circulation and Its Variability in CESM2 and Other CMIP Models. Issue 13 (25th June 2020) - Simpson, Isla R.; Bacmeister, Julio; Neale, Richard B.; Hannay, Cecile; Gettelman, Andrew; Garcia, Rolando R.; Lauritzen, Peter H.; Marsh, Daniel R.; Mills, Michael J.; Medeiros, Brian; Richter, Jadwiga H.
Abstract: The Community Earth System Model 2 (CESM2) is the latest Earth System Model developed by the National Center for Atmospheric Research in collaboration with the university community and is significantly advanced in most components compared to its predecessor (CESM1). Here, CESM2's representation of the large‐scale atmospheric circulation and its variability is assessed. Further context is providedthrough comparison to the CESM1 large ensemble and other models from the Coupled Model Intercomparison Project (CMIP5 and CMIP6). This includes an assessment of the representation of jet streams and storm tracks, stationary waves, the global divergent circulation, the annular modes, the North Atlantic Oscillation, and blocking. Compared to CESM1, CESM2 is substantially improved in the representation of the storm tracks, Northern Hemisphere (NH) stationary waves, NH winter blocking and the global divergent circulation. It ranks within the top 10% of CMIP class models in many of these features. Some features of the Southern Hemisphere (SH) circulation have degraded, such as the SH jet strength, stationary waves, and blocking, although the SH jet stream is placed at approximately the correct location. This analysis also highlights systematic deficiencies in these features across the new CMIP6 archive, such as the continued tendency for the SH jet stream to be placed too far equatorward, the North Atlantic westerlies to be too strong over Europe, the storm tracks as measured by low‐level meridional wind variance to be too weak and a lack of blocking in the North Atlantic sector. Key Points: CESM2 is compared to CESM1 and other CMIP5 and CMIP6 models and ranks highly in many regards Jets, storm tracks, stationary waves, divergent circulation, NAM, SAM, NAO, and blocking are assessed CESM2 has improvements in storm tracks and NH winter circulation but degradations in SH circulation